Preventing spread of photovoltaic fire by reducing the heat transfer rate within a photovoltaic module - Tung, Li Song (Nanyang Technological University, 2024)
The use of solar energy has been increasing in the recent years. Photovoltaics are being integrated into more structures. Instead of the conventional way of placing them on top of roofs, photovoltaics is slowly being integrated into roofs, facades, walls and even windows. These new integration of photovoltaics into the existing structure of buildings are called Building Integrated Photovoltaics (BIPV), which are slightly different from the traditional system of Building Applied Photovoltaics (BAPV) where the photovoltaics are added on the exterior of buildings. With an increasing number of photovoltaics installation, fire safety of the photovoltaics is a concern. Traditional BAPVs have a layer of glass on its back. Glass has very low thermal conductivity, which means that heat transfer rate of glass is very low. Additionally, in BAPV system, in an event of fire break out, there is still a layer of concrete roof between the photovoltaics and the building. This layer of concrete can help prevent the spread of fire from the building to the photovoltaics, or vice versa. One concern of BIPV, as compared to BAPV, is weight. Since BAPV are placed on top of roofs, they do not have too much of a weight limitation, hence using a thick layer of glass as thermal insulation is alright for BAPV, but not BIPV. In view of this, for BIPVs, the thick layer of glass must be either reduce or replace without compromising the heat transfer rate of the photovoltaic. Intumescent materials are materials that expand when exposed to heat and are used on steel structures, commercially, as a form of fire protection. Additionally, Polybenzoxazine is observed to have a char yield at 800℃ of about 30% which is way higher than commercial polymer resins of about 7%[1]. This means that Polybenzoxazine does show some potential as a flame-retardant material. A new system has been implemented which includes replacing and reducing the thickness of the glass piece in traditional photovoltaics and adding a layer of intumescent coating or Polybenzoxazine coat. This aims to reduce the heat transfer rate of the photovoltaic, making it less of a fire hazard. Both coating shows improvement in fire performance with the Polybenzoxazine having more promising results.